Self-reported osteoporosis prevention in inhaled corticosteroid users in community pharmacy setting. (22nd May 2015) - Chan, Valerie; Cave, Andrew J; Banh, Hoan Linh
Objectives: The use of inhaled corticosteroids is the standard maintenance therapy in asthma therapy and as adjunct therapy in moderate to severe chronic obstructive pulmonary disease. A dose-related increase in fracture risk is associated with inhaled corticosteroid use; there is an inverse relationship between bone mineral density and duration and cumulative dose of inhaled corticosteroid. Adequate intake of calcium and vitamin D are cornerstones of osteoporosis prevention. The objectives are to assess whether the proportion of patients receiving inhaled corticosteroids are taking calcium and vitamin D; the association between long-term inhaled corticosteroid use and abnormal bone mineral density or fractures; and how many qualified patients received bone mineral density scans. Methods: Patients who filled a prescription for inhaled corticosteroids at selected community pharmacies across Alberta were recruited for a survey of their osteoporosis prevention activities. Results: A total of 256 patients from 12 community pharmacies were included. The average age was 60 ± 17.4 years with 65% female. There were 21%, 51%, and 28% of patients on high, medium, and low dose inhaled corticosteroids, respectively. Only 17% of patients >50 years old received recommended calcium and vitamin D supplementation and 87 (73%) of the qualified patients received bone mineral density scan. Conclusion: Osteoporosis prevention in inhaled corticosteroid users is currently poorly addressed. More promotion is needed to raise pharmacist awareness of the risks of inhaled corticosteroids.